2014
DOI: 10.7454/jki.v17i2.401
|View full text |Cite
|
Sign up to set email alerts
|

Pengalaman Keluarga dalam Merawat Lanjut Usia dengan Diabetes Mellitus

Abstract: AbstrakMerawat lansia Diabetes Melitus (DM) menimbulkan dampak terhadap fisik, emosi, sosial dan ekonomi. Penelitian bertujuan untuk mendapatkan pemahaman yang mendalam tentang arti dan makna pengalaman keluarga dalam merawat lansia DM di kota Tasikmalaya, Jawa Barat. Penelitian fenomenologi deskriptif ini melibatkan delapan partisipan yaitu caregiver utama lansia DM yang didapatkan dengan teknik criterion sampling. Data diperoleh melalui wawancara mendalam dan catatan lapangan yang dianalisis dengan menerapka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Other studies showed that the family caregivers who care for people with diabetes have health problems themselves or physical and psychological disorders. This has the impact of them having a decreased ability to carry out the health task of caring for people with diabetes (Badriah, Wiarsih, & Permatasari, 2017). Furthermore, the failure of a family caregiver in terms of diabetes self management has an impact on their health status.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that the family caregivers who care for people with diabetes have health problems themselves or physical and psychological disorders. This has the impact of them having a decreased ability to carry out the health task of caring for people with diabetes (Badriah, Wiarsih, & Permatasari, 2017). Furthermore, the failure of a family caregiver in terms of diabetes self management has an impact on their health status.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, several factors influence caregiver readiness: commitment, capacity, and knowledge in providing care to patients’ families. In addition, to motivate and spiritually support the family members, a caregiver must have a commitment and capacity to carry out their role well [ 38 ]. The commitment includes maintaining the relationship with the patient, motivation in caregiving, and spiritual support, while their capacity as a caregiver refers to considering their health status, ability to maintain a role, financial resources, and knowledge [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3 Due to aging, older people with T2DM experienced a loss of independent 4 and cognitive impairment 5 , it can lead to increase their dependent up to their family. 6,7 Diabetes mellitus is incurable disease that require critical attention, elderly people with T2DM need support from family members as a caregivers in order to carry out their activities that are useful in controlling their blood sugar levels 8 . Therefore, the family caregivers play an important role in providing long-term care for elderly with T2DM.…”
Section: Introductionmentioning
confidence: 99%